2010
DOI: 10.1208/s12248-010-9219-8
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Tissue Pharmacokinetics of Intravesical Mitomycin C and Suramin in Dogs

Abstract: Abstract. Suramin, at non-cytotoxic doses, reverses chemoresistance and enhances the activity of mitomycin C (MMC) in mice bearing human bladder xenograft tumors. The present study evaluated the pharmacokinetics of the intravesical suramin and MMC, alone or in combination, in dogs. Animals received either high dose suramin (20 mg/ml), low dose suramin (6 mg/ml), MMC (2 mg/ml), or combination of low dose suramin and MMC, instilled for 2 h. The dosing volume was 20 ml. All groups showed dilution of drug levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…However, the drug concentration at each depth of the skin has been predicted using various mathematical equations [13][14][15][16][17][18]. We previously reported that the cutaneous disposition of topically applied drugs could be predicted using the difference method based on Fick's 2 nd law of diffusion, and also that the average drug concentration in the stratum corneum and viable epidermis/dermis could be determined separately [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the drug concentration at each depth of the skin has been predicted using various mathematical equations [13][14][15][16][17][18]. We previously reported that the cutaneous disposition of topically applied drugs could be predicted using the difference method based on Fick's 2 nd law of diffusion, and also that the average drug concentration in the stratum corneum and viable epidermis/dermis could be determined separately [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous in vitro investigations showed a duplication time of 56 ± 3 and 59 ± 2 hours for RT4 and RT112 experimental transitional tumor cell lines, respectively, far lower than the expected 7 days (10, 11).…”
Section: Optimizing Schedule Of Administrationmentioning
confidence: 61%
“…Penetration of intravesical drugs is characterised by a steep drop in concentration across the bladder wall due to limited tissue permeability that leads to low drug concentrations in deep tissue layers where high drug concentrations are needed to combat tumours with limited chemosensitivity [5,6,11,33]. Wientjes et al [6] reported an exponential decline in DOX concentration in the perfused tissues below the urothelium following intravesical administration of DOX in patients and a high degree of inter-patient variability.…”
Section: Discussionmentioning
confidence: 99%
“…High drug concentrations are needed at depth in the bladder wall to treat invasive tumours that reside there [9]. The urothelium, which lines the bladder lumen, acts as a transport barrier that restricts passage of molecules such as urea and ammonia from the urine (as well as intravesical drugs) into systemic circulation [10][11][12]. In addition, glycosaminoglycans comprising the mucin layer overlying the urothelium may further inhibit transport of intravesical substances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation